The marginal propensity to consume during the COVID-19 pandemic: Evidence from Thailand and Vietnam - Dzung Bui; Lena Dräger; Bernd Hayo; Giang Hong Nghiem (Philipps-University Marburg, School of Business and Economics, 2022)
In evaluating surveys conducted in Thailand and Vietnam during the COVID-19 pandemic, we find that the marginal propensity to consume is significantly larger for positive than for negative income shocks. This result contradicts a prediction from the lifecycle permanent income model with borrowing constraints as well as empirical evidence from industrialized countries. However, our finding is consistent with Kahneman and Tversky's prospect theory, according to which the combination of income uncertainty and loss aversion can induce households to react more strongly to positive than to negative shocks.
Keywords: E62; E71; D12; D83; H31; 330; Marginal propensity to consume (MPC); Unanticipated income shocks; COVID-19; Thailand; Vietnam